Pharmacological treatment of treatment-resistant depression: towards evidence-based recommendations - Jerotić, Stefan (Medical Research, 2024)
Depression, a major global public health concern and leading cause of disability, necessitates effective management. This paper, part of the development of comprehensive guidelines for treating unipolar depression in Serbia, delves into the pharmacological treatment of this treatment-resistant depression, focusing on augmentative and switching strategies, aiming to address the lack of response to standard treatments. The focus lies on the efficacy and tolerability of various pharmacological agents, aimed at facilitating informed clinical decisions  In TRD, augmentation strategies involving atypical antipsychotics, NMDA antagonists, mood stabilizers, and other compounds are examined. Finally, the importance of an individualized approach in deciding between augmentation and switching strategies is emphasized. This comprehensive review aims to inform treatment guidelines and encourages a collaborative approach, considering individual patient factors, to improve the quality of care for individuals with treatment-resistant depression.
Keywords: treatment-resistant depression; pharmacological treatment; guidelines